소셜 미디어에서 나타나는 신체 긍정주의와 표현 방법, 여성의 주관적 신체 사이즈 인식이 기분 상태와 외모 만족도에 미치는 영향 - 이민선; Minsun Lee; 이현화; Hyun-hwa Lee (Fashion & textile research journal, 2020)
Body positivity has emerged among young social media users with the purpose of enhancing a positive body image. In the social media environment, body positivity is frequently presented in the forms of female models' images and/or words that represent individual attitudes toward the female body. The media effects on female viewers' body image differs based on the viewers' perceptions of their own body size. This experimental study examined how body positivity and types of expression on social media influence women's mood and appearance satisfaction by subjective body size. We randomly assigned to 415 young and middle-aged females to one of six experimental conditions which contained three images and three vignettes, each reflecting non-body positivity, body positivity, and control. We used a 3 (body positivity: non-body positivity vs body positivity vs. control) × 2 (types of body positivity expression on media: images vs vignettes) × 2 (subjective body size: under/normal weight vs overweight/obese) between-subject design. The results of MANCOVA revealed the significant main effects of subjective body size on women's mood and appearance satisfaction. There was a significant interaction effect of body positivity and subjective body size on appearance satisfaction. The stimuli representing body positivity caused positive psychological effects for women who perceive themselves being in the under/normal weight range.